Dizziness, light-headedness or a clot-in-transit: obtaining a history and physical exam is both a science and an art - Abhinav Hoskote; Shreya Sudadi; Brent Dembo; Michelle Consolini; Rahul Kashyap (European Journal of Case Reports in Internal Medicine)
Introduction: Venous thromboembolism (VTE) rarely presents with dizziness as the primary complaint, which can delay diagnosis. We report a rare case of dizziness as the chief complaint for a clot-in-transit and extensive bilateral pulmonary emboli. Case description: A 70-year-old woman presented to the emergency room (ER) with dizziness and a fall, without reporting loss of consciousness. Her symptoms included positional dizziness, tinnitus and visual darkness, alongside prior exertional fatigue and dull chest pressure. Despite a history of left leg oedema and inconsistent use of medications for hypertension and diabetes, initial examinations suggested vestibular neuritis and decompensated heart failure, confirmed by echocardiogram findings and response to prednisone. While hospitalised, she experienced pre-syncope after showering, initially deemed vasovagal. However, exertional hypotension led to further investigation, revealing right heart strain. Ultrasound identified a left popliteal deep vein thrombosis, and a computed tomography (CT) angiogram confirmed extensive bilateral pulmonary emboli with right heart strain. Cardiology discovered large, mobile thrombi in transit in the heart, necessitating an urgent mechanical thrombectomy. Following treatment, her pulmonary pressure improved, and she was discharged on anticoagulation medicine. One month later, an echocardiogram showed normalised heart function. Conclusion: This case highlights the importance of differentiating dizziness from pre-syncope, as exertional pre-syncope can indicate an obstructive physiology such as VTE. Cognitive bias can obscure diagnosis in atypical presentations. A pulmonary embolism response team could improve management of these cases, where prompt diagnosis and treatment are essential for favourable outcomes.